Interleukin-2 receptor signaling acts as a checkpoint that influences the distribution of regulatory T cell subsets - Acacia N. Shouse; Alejandro V. Villarino; Thomas R. Malek (iScience)
Summary: Regulatory T cells (Tregs) require IL-2 for survival in the periphery, yet how IL-2 shapes Treg heterogeneity remains poorly defined. Here we show that inhibition of IL-2R signaling in post-thymic Tregs leads to a preferential early loss of circulating Tregs (cTregs). Gene expression of cTregs was more dependent on IL-2R signaling than effector Tregs (eTregs). Unexpectedly, ablation of IL-2R signaling in cTregs resulted in increased proliferation, expression of eTreg genes, and enhanced capacity to develop into eTregs. Thus, IL-2R signaling normally acts as a checkpoint to maintain cTreg homeostasis while restraining their development into eTregs. Loss of IL-2R signaling also alters the distribution of eTreg subsets, with increased IFNγR1+ eTregs and CXCR5+ PD-1+ T follicular regulatory (TFR) cells but decreased intestinal RORγt+ TR17 cells. These changes lower eTreg suppressive function supporting expansion of IFNγ-secreting T effector cells. Thus, IL-2R signaling also safeguards Treg function and licenses differentiation of specialized eTregs.